2019
DOI: 10.3390/medicina55050213
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Salivary Level of Cortisol in Patients with Oral Lichen Planus: A Meta-Analysis

Abstract: Background and objective: Cortisol, as the main human glucocorticoid, is considered to be a biological marker of stress and anxiety. Since it is known that oral lichen planus (OLP) can appear and worsen during stressful events, cortisol levels have been previously studied in OLP patients. The present meta-analysis aims to assess the salivary concentration of cortisol in OLP patients compared to healthy controls. Materials and methods: Web of Science, PubMed, Cochrane Library, and Scopus databases were searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
1
11
0
3
Order By: Relevance
“…Se ha reportado que el estrés produce un desgaste y desregulación fisiológica debido a que eleva los niveles de cortisol (4). De tal forma que si el paciente presenta repetidos o continuos episodios de estrés se activan continuamente mecanismos compensatorios fisiológicos, lo que podría desencadenar o alterar el curso de enfermedades orales (19), y en consecuencia ocasiona un efecto negativo sobre la salud oral.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Se ha reportado que el estrés produce un desgaste y desregulación fisiológica debido a que eleva los niveles de cortisol (4). De tal forma que si el paciente presenta repetidos o continuos episodios de estrés se activan continuamente mecanismos compensatorios fisiológicos, lo que podría desencadenar o alterar el curso de enfermedades orales (19), y en consecuencia ocasiona un efecto negativo sobre la salud oral.…”
Section: Discussionunclassified
“…Se define a enfermedades orales asociadas a estrés como aquellas enfermedades de la mucosa oral que se ven agravadas, exacerbadas o desarrolladas por estados emocionales tales como estrés, ansiedad y/o depresión (2,3). Entendiendo por estrés, a un factor psicológico que causa una elevación en los niveles de cortisol, asociado a su vez, con un desbalance de citoquinas las cuales pueden predisponer al desarrollo de enfermedades autoinmunes orales (4). Las características clínicas y sintomáticas de estas enfermedades interfieren con el comer, hablar o con la correcta higiene oral.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Salivary cortisol values have been widely studied in relation to the effects of stress- and anxiety-related psychological factors on immune diseases. Elevated salivary cortisol values have been observed in patients diagnosed with OLP than in those without this disease [ 17 , 18 , 19 ], and it has been suggested that there is a link between high cortisol levels and psychological strains as triggering factors of OLP [ 20 ]. Given reports that stress can be responsible for the recurrence of OLP, cortisol has been proposed as a possible diagnostic marker for this disease [ 21 ].…”
Section: Biomarkers In Saliva In Different Oral Diseasesmentioning
confidence: 99%
“…Many authors have suggested salivary cortisol as a biomarker in OLP [65][66][67][68][69][70]. Cortisol is considered a biological marker of stress and anxiety, the variation of which can alter cytokine profiles [71].…”
Section: Oral Lichen Planusmentioning
confidence: 99%